A study of the cenopopulations and ontogenetic structure of Adonis wolgensis in the Akmola region - Zhumagul, M.Z.; Mukhtubayeva, S.K.; Kubentayev, S.A.; Izbastina, К.S.; Abubakirova, N.B.; Rustemova, A.D. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The article presents the results of study of six cenopopulations of rare medicinal plant Adonis wolgensis Steven ex DC. (Ranunculaceae) in Akmola region of Northern Kazakhstan. Ecological-phytocenotic characterization was given and ontogenetic structure of cenopopulations was studied. It is established that in the studied region Adonis wolgensis grows among steppe grasses, in bushes, occasionally on forest edges and on forest lawns. In general, the condition of the studied Adonis wolgensis cenopopulations is satisfactory. Analysis of age spectra showed that cenopopulations not or slightly affected by anthropogenic impact are characterized by a spectrum in which the absolute maximum falls on the age states of the pre-generative period. In the four cenopopulations, a significant proportion of individuals are in the young generative state, indicating their capacity for self-renewal. This ensures the stability of the species in the plant communities of the study areas. The condition of two cenopopulations is assessed as degrading, and urgent measures are needed to preserve them and restore their numbers. Cattle grazing in cenopopulations leads to a decrease in plant viability and suppression of seed reproduction. To preserve the species it is necessary to limit grazing, prohibit collection of raw materials, develop methods of cultivation in culture, organize reproduction of the species in industrial volumes, and strengthen protection measures. The results obtained have provided new information on the status of the species in Northern Kazakhstan and serve as a reliable basis for its further conservation.
Ақмола облысы бойынша Adonis wolgensis ценопопуляцияларын және онтогенетикалық құрылымын зерттеу
Изучение ценопопуляций и онтогенетической структуры Adonis wolgensis в Акмолинской области
Keywords: Adonis; Flora of Kazakhstan; rare species; biodiversity conservation; Northern Kazakhstan; state of cenopopulations.